Passive islanding detection technique for synchronous generators based on performance ranking of different passive parameters. Issue 17 (3rd November 2017) - Raza, Safdar; Arof, Hamzah; Mokhlis, Hazlie; Mohamad, Hasmaini; Illias, Hazlee Azil
Abstract : Islanding detection is important for the protection of any distribution system supported by distributed energy resources. In this work, a number of islanding and non‐islanding events are simulated to prioritise 16 different passive parameters on the basis of performance analysis. Among the parameters tested, the rate of change of frequency over reactive power (d f /d q ) attains the highest accuracy and consequently, a new passive technique is proposed that employs d f /d q as discriminative feature. An extended study is carried out to further test the ability of the technique to differentiate the islanding from the non‐islanding events of similar signatures, such as load variation, capacitor switching, faults and induction motor starting. The simulation results confirm that the technique is proficient enough to identify islanding from non‐islanding events that cause minute disturbances in the power supply network.